Financial Literacy Among Affirmative University Students - Dwi Wulandari; Bagus Shandy Narmaditya (AL-ISHLAH: Jurnal Pendidikan, 2022)
The research aims at measuring the students’ financial literacy who received affirmation of Higher Education Scholarships which coming from remote areas. The measurement is important toward how financially literate the students are in making financial decisions and what the determinants of financial literacy. Further, the measurement will provide information on how to increase the financial literacy of the students given that, after completing their studies, they are expected to significantly improve the financial literacy in their hometown as policymakers and leaders. Based on the findings, it can be concluded that the students have a low level of financial literacy. This problem can be addressed by reaching out to all the students in Indonesia, especially those in remote areas to help them understand the concept of financial literacy and enable to make a good decision as consumers and investors. Also, need to help the students understand the importance of financial literacy and convince that having this skill improve their welfare in the future. Moreover, lecturer should be aware of the different learning styles of individuals. For example, for students who come from remote areas, the topic should be delivered in a fun and easy way by using relatively simple language.